Coagulopathy post peritoneovenous shunt. - LeVeen, H H (1987)
In 1942, 53% of medically treated patients with cirrhosis were dead 6 months after the onset of ascites. Only 30% survived 1 year. This dismal outlook has improved only slightly with advances in medicine. Yet, some internists reject the peritoneovenous shunt (PVS) for this fatal condition even if they are aware that a diminished blood volume causes the abnormal sodium retention responsible for ascites. Their objections are based on life-threatening complications of PVS, especially post shunt coagulopathy (PSC). Blood shed into the peritoneal cavity becomes incoagulable. Such blood is immediately coagulated by a protocoagulant (soluble collagen) and concurrently lysed by tissue plasminogen activator (TPA) secreted by the peritoneal serosa. Wide zones of lysis surround peritoneal tissue placed on fibrin plates. Large volumes of ascitic fluid infused into circulating blood simulates the fate of blood shed into the peritoneal cavity with lysis playing the major role. Addition of ascitic fluid to normal platelet-rich plasma in vitro initiates clot lysis on thromboelastogram (TEG). Epsilon-aminocaproic acid (EACA) counteracts this lysis. EACA and clotting factors normalize the TEG and arrest PSC. Disposal of ascitic fluid at surgery prevents or ameliorates PSC. Mild PSC was encountered only twice in 150+ consecutive patients (1.3%) with only one case being clinically significant (0.6%). Severe PSC occurred seven times in 98 early shunt patients whose ascitic fluid was not discarded. Severe PSC requires shunt interruption and control of bleeding with clotting factors and EACA. Peritoneal lavage with saline prevents the recurrence of PSC on reopening the shunt. In four patients, EACA and clotting factors were adequate to arrest coagulopathy. Three earlier patients died of PSC before its cause and treatment were understood. Proper management eliminates this life-threatening complication, and PSC cannot be considered a deterrent to PVS. Disseminated intravascular coagulopathy (DIC) is produced in experimental animals only by the injection of thrombin or thromboplastin. PSC is a distinct entity differing from DIC; EACA and not heparin is the antidote for PSC.